Unusual reintervention through a fistula for ampullary penetration of a plastic stent in malignant distal biliary obstruction. Issue 2 (27th January 2019) - Sugiura, Ryo; Kuwatani, Masaki; Sakamoto, Naoya
Abstract : Watch a video of this article